Aktualny Stan Wiedzy o Kształtowaniu Wytrzymałościowym Konstrukcji - Z. Wasiutyński; A. Brandt (Engineering Transactions, 1962)
The paper contains an analysis of various trends in the domain of design of structures, special stress being laid on contemporary works. In the introduction, the authors point out the importance of design problems and the lack of coordination between various scientific centres. The second chapter is devoted to a historical survey. of more important publications since GALILEO's work published in 1638 until the recent times. This survey is supplemented by a desciption of the development of particular historical trends and their features. A list of contemporary scientists working on design problems in Poland and abroad is added. The third chapter is devoted to the minimum weight design. In this field the work is continued by W. Prager and his group. The form of the structure is determined on the basis of the criterion of minimum material volume at the plastic collapse of the structure. It is assumed that the material is homogeneous, clastic and perfectly plastic. These works apply chiefly to metal structures. In the fourth chapter the design of statically indeterminate structures on the basis of uniform strength conditions is described and analysed. This problem is the object of the work of J. M. Rabinowitch and a large group of his co-workers. The uniform strength condition is realized by making the extremum stress in cross-sections equal to the admissible ones. The object of considerations are sets of structures of the same geometric configuration of elements and various support conditions. The design consists in selecting from- a set of structures the one satisfying the condition of minimum material consumption. The fifth chapter concerns the minimum elastic potential design for a constant material volume. This is the object of the work of Z. WASIUTYNSKI and his co-workers. The aim is to determine such a structure that the state of stress or strain is ordered to obey a prescribed law. The design criterion is that of uniform unit potential in the entire structure, which is equivalent to that of minimum of potential of elastic deformation for constant material volume. Assuming of the structure the inverse elastic energy, for the measure of rigidity the critetion thus formulated, is equivalent to that of maximum rigidity design. These considerations do not exceed the elastic range of the material. The results apply chiefly to the civil engineering problems. The sixth chapter is devoted to sone other design methods. The first of them is being developed by S. KAUFMAN and his co-workers and concerns the determination of the form of prestressed. structures, Also B. KOPYCIŃSKI is concerned with the problem of design of prestressed beams. The works of H. H. HILTON contain solutions of design problems from the viewpoint of the theory of probability, the strength properties of the material and the structure and also the load being. treated as quantities obeying statistical laws. The list of publications used for the preparation of this survey of design problems contains 166 items and is given at the end of the paper.